The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1103/physreva.59.808
|View full text |Cite
|
Sign up to set email alerts
|

Quantum theory of the two-photon mazer: Emission probability

Abstract: We apply the concept of the mazer to the two-photon process and propose the idea of the two-photon mazer. We establish the general quantum theory of the two-photon mazer and calculate its emission probability in the special case of a mesa mode function. We study not only the case in which the cavity field is initially in a number state, but also the case in which the cavity field is initially in a coherent state. Under the condition of an initial coherent field, the emission probability shows the collapse-revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…Löffler et al [7] showed also that the mazer may be used as a velocity selection device for an atomic beam. The mazer concept was extended by Zhang et al [8,9,10], who considered two-photon transitions [8], three-level atoms interacting with a single cavity [9] and with two cavities [10]. Collapse and revival patterns with a mazer have been computed by Du et al [11].…”
Section: Introductionmentioning
confidence: 99%
“…Löffler et al [7] showed also that the mazer may be used as a velocity selection device for an atomic beam. The mazer concept was extended by Zhang et al [8,9,10], who considered two-photon transitions [8], three-level atoms interacting with a single cavity [9] and with two cavities [10]. Collapse and revival patterns with a mazer have been computed by Du et al [11].…”
Section: Introductionmentioning
confidence: 99%
“…[726] in the case of a mesa function (the problem is analytically solvable in this case). Since its introduction, the maser action has been generalized to various setups; bimodal cavities [727,728], two-photon transitions [729,730], Λ atoms [731,732], and V atoms [733,734]. Effects of quantized motion in the STIRAP scheme was analyzed in [735], and it was particularly found that the adiabatic passage breaks down for sufficiently slow atoms and then a series of tunneling resonances appears.…”
Section: Quantized Atomic Motionmentioning
confidence: 99%
“…At the present time, no work has been devoted to know whether the revivals predicted by Zhang et al [7] for the two-photon mazer may also be suppressed by use of an appropriate initial state of the atom-field system. An answer to this question is given at the end of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [7] extended the concept of the mazer to the two-photon process by proposing the idea of the two-photon mazer. Their work was focused on the study of its induced emission probability in the special case of the mesa mode function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation